2008
DOI: 10.1007/s11427-008-0116-7
|View full text |Cite
|
Sign up to set email alerts
|

The targeting expression of the vascular endothelial growth factor gene in endothelial cells regulated by HRE.ppET-1

Abstract: The success of gene therapy depends largely on the efficacy of gene delivery vector systems that can deliver genes to target organs or cells selectively and efficiently with minimal toxicity. Here, we show that by using the HRE.ppET-1 regulatory element, we were able to restrict expression of the transgene of vascular endothelial growth factor (VEGF) to endothelial cells exclusively in hypoxic conditions. Eukaryotic expression vectors such as pEGFP-HRE.ppET-1, pcDNA3.1-VEGF+Pa, pcDNA3.1-ppET-1+ EGF+Pa, and pcD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…1a, the predicted length of each qPCR product was confirmed by agarose gel electrophoresis (148, 106, 92 and 60 bp which correspond to the predicted length of VEGF, VEGFR-1, VEGFR-2 and GAPDH mRNA, respectively). In agreement with previous results demonstrating that hypoxia is a potent stimulus for VEGF upregulation in HUVEC (Avouac et al 2008;Cho et al 2008;Liu et al 2009;Nilsson et al 2004;Takata et al 2008;Zheng et al 2008), we found that hypoxia caused a drastic increase in the level of the VEGF mRNA (∼163%, **P < 0.01; Fig. 1b) while we also determined a significant decrease in the expression of both VEGFR-1 (∼58%, **P<0.01; Fig.…”
Section: Hypoxia Effects On Vegf and Its Receptorssupporting
confidence: 93%
See 2 more Smart Citations
“…1a, the predicted length of each qPCR product was confirmed by agarose gel electrophoresis (148, 106, 92 and 60 bp which correspond to the predicted length of VEGF, VEGFR-1, VEGFR-2 and GAPDH mRNA, respectively). In agreement with previous results demonstrating that hypoxia is a potent stimulus for VEGF upregulation in HUVEC (Avouac et al 2008;Cho et al 2008;Liu et al 2009;Nilsson et al 2004;Takata et al 2008;Zheng et al 2008), we found that hypoxia caused a drastic increase in the level of the VEGF mRNA (∼163%, **P < 0.01; Fig. 1b) while we also determined a significant decrease in the expression of both VEGFR-1 (∼58%, **P<0.01; Fig.…”
Section: Hypoxia Effects On Vegf and Its Receptorssupporting
confidence: 93%
“…Our study shows that hypoxia is a potent stimulus for VEGF expression and production, confirming previous findings in HUVEC (Avouac et al 2008;Cho et al 2008;Liu et al 2009;Nilsson et al 2004;Takata et al 2008;Zheng et al 2008). Hypoxia has been proposed to play an important role in the regulation of VEGF receptor expression although previous studies have yielded conflicting results.…”
Section: Hypoxia Affects Vegf and Its Receptorssupporting
confidence: 90%
See 1 more Smart Citation